Methane Bubble Ascent within Fine-Grained Cohesive Aquatic Sediments: Dynamics and Controlling Factors - Sirhan, Shahrazad Tarboush; Katsman, Regina; Lazar, Michael (Environmental science & technology, 2019)
Methane (CH4) is a potent greenhouse gas. Its release from aquatic sediments to the water column and potentially to the atmosphere, is a subject of great concern. A coupled macroscopic single-bubble mechanical/reaction-transport numerical model was used to explore the ascent of a mature CH4 bubble toward the seafloor in muddy aquatic sediment. Two bubble ascent scenarios were demonstrated: stable and dynamic. For small effective overburden loads (≤11 kPa), stable ascent is followed by dynamic ascent (which has not been previously demonstrated to the best of the our knowledge). This ultimately leads to the bubble being released to the water column. Higher effective overburden loads induce only stable bubble ascent, which stops at the gas horizon frequently observed below the seafloor. The depth of the gas horizon increases, while bubble rise velocity decreases with an increase in the overburden load. It is shown that the bubble migration scenario is managed predominantly by inner bubble pressure, which defines a bubble solute exchange with ambient porewaters. Predicting a bubble ascent scenario in muddy sediment will further allow estimation of CH4 emission to the atmosphere and evaluation of changes in the effective mechanical properties of aquatic sediment due to the ascending bubbles.